Nurse managers and patient safety: development and implementation of a European training program - Tsitsi, Theologia; Efstathiou, Georgios; Andeou, Panayiota; Palese, Alvisa; Longhini, Jessica; Schubert, Maria; Zigan, Nicole; De Wolf-Linder, Susanne; Stemmer, Renate; Ströhm, Christina; Papastavrou, Evridiki (My University, 2023)
Modern health care systems need dynamic leaders, empowered with current and evidenced based practices and knowledge. Nurse managers belong to the above leaders. Their role in ward management is crucial. For this reason, nurse managers need to be empowered in order to become acquainted with skills and knowledge that will facilitate them to play their managerial role in a satisfactory way. More specifically, the need to have skills on safe staffing, communication, conflict management and rationing of nursing care. The present article describes the process that was followed for the development of an online educational tool, for the empowerment of nurse managers. The development of the tool was part of the Erasmus+ project Nurse Managers For Safety. Four countries and five partners (Cyprus, Italy, Switzerland and Germany) formed the research consortium (four universities and a technology-expert partner). The four universities, through literature review and focus groups discussion, designed the content of the online tool (scripts, power point presentations, videos), in various languages with additions subtitles. The online tool includes a selection of topics and challenges which nurse managers come across with daily. The pilot implementation of the tool has indicated the importance of such projects and the complexity of the responsibilities nurse managers have.